Neuropilin‐1 is present on Foxp3+ T regulatory cell‐derived small extracellular vesicles and mediates immunity against skin transplantation. Issue 6 (8th June 2022) - Campos‐Mora, Mauricio; De Solminihac, Javiera; Rojas, Carolina; Padilla, Cristina; Kurte, Mónica; Pacheco, Rodrigo; Kaehne, Thilo; Wyneken, Úrsula; Pino‐Lagos, Karina
Abstract: Among the mechanisms of suppression that T regulatory (Treg) cells exert to control the immune responses, the secretion of small extracellular vesicles (sEV) has been recently proposed as a novel contact‐independent immunomodulatory mechanism. Previous studies have demonstrated that Treg cells produce sEV, including exosomes, able to modulate the effector function of CD4+ T cells, and antigen presenting cells (APCs) such as dendritic cells (DCs) through the transfer of microRNA, cytokines, the production of adenosine, among others. Previously, we have demonstrated that Neuropilin‐1 (Nrp1) is required for Tregs‐mediated immunosuppression mainly by impacting on the phenotype and function of effector CD4+ T cells. Here, we show that Foxp3+ Treg cells secrete sEV, which bear Nrp1 in their membrane. These sEV modulate effector CD4+ T cell phenotype and proliferation in vitro in a Nrp1‐dependent manner. Proteomic analysis indicated that sEV obtained from wild type ( wt ) and Nrp1KO Treg cells differed in proteins related to immune tolerance, finding less representation of CD73 and Granzyme B in sEV obtained from Nrp1KO Treg cells. Likewise, we show that Nrp1 is required in Treg cell‐derived sEV for inducing skin transplantation tolerance, since a reduction in graft survival and an increase on M1/M2 ratio were found in animals treated with Nrp1KO Treg cell‐derived sEV. Altogether, this study describes for the first time that Treg cells secrete sEV containing Nrp1 and that this protein, among others, is necessary to promote transplantation tolerance in vivo via sEV local administration.